AP4 transcription factor binding site is a repressor element in ek2 promoter of human liver carcinoma cell line, HepG2 - Teh, Zhi Hui; Kuan, Chee Sian; Lim, Boon Huat; Too, Wei Cun See; Few, Ling Ling (Penerbit Universiti Kebangsaan Malaysia, 2017)
Ethanolamine kinase (EK) is the first enzyme in the Kennedy pathway for the biosynthesis of phosphatidylethanolamine. Although EK has been reported to be involved in phospholipid biosynthesis, carcinogenesis, cell growth, muscle development and sex determination during embryonic development, little is known about its transcriptional regulation by endogenous or exogenous signals. Human EK exists as EK1, EK2α and EK2β isoforms, encoded by two separate genes, named ek1 and ek2. Compared to ek1 gene, ek2 is expressed at a higher level in liver and EK2 isoforms also accept choline as substrate besides ethanolamine, which could contribute to liver carcinogenesis. The main aim of this study was to analyze and characterize the human ek2 promoter in cultured mammalian cells. Human ek2 (2011 bp) promoter was cloned into reporter vector, pGL4.10 [luc2] and the promoter activities were studied in human liver carcinoma (HepG2 cells). Sequence analyses showed that ek2 promoter contains numerous putative transcription factor binding sites including AP4 and it is devoid of a recognizable consensus TATA box but it contains a high number of guanine (G) and cytosine (C) nucleotides. PCR mutagenesis of three nucleotides at E-box motif of AP4 transcription binding site located between -293 and -276 of ek2 promoter was successfully performed to show that AP4 transcription factor binding site acts as a repressive element in the regulation of ek2 expression. AP4 upregulation has been implicated in bad prognosis of carcinoma, therefore the regulatory role of AP4 binding site reported in this study could be a link between ek2 and carcinogenesis. Although further studies need to be carried out to understand and to determine the repression mechanism of AP4 in ek2 promoter, the characterization and analysis of ek promoter performed in this study provide important understanding of its basal transcriptional regulation which would allow us to control ek expression levels in pathologic conditions that involve this gene.